1974
DOI: 10.1017/s0022112074001297
|View full text |Cite
|
Sign up to set email alerts
|

Shock-wave structure and intermolecular collision laws

Abstract: The nonlinear Boltzmann equation has been solved for shock waves in a Max-wellian gas for eight upstream Mach numbers M1 ranging from 1·1 to 10. The numerical solutions were obtained by using Nordsieck's method, which was revised for use with the differential cross-section corresponding to an intermolecular force potential following an inverse fifth-power law. The accuracy of the calculations of microscopic and macroscopic properties for this collision law is comparable with that for elastic spheres published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

1980
1980
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 9 publications
1
1
0
1
Order By: Relevance
“…The calculations have shown that this relation is not observed only in the area close to U 2 . The parabolic dependence up xx against velocity is identical to the proportional dependence of the transverse stress against the gas density in the shock wave described in [2,3], The results analogous to (2) were obtained also for the gas consisting of hard sphere molecules (k = oo) and in the case when k = 10. When k = oo the main difference is that coefficient 40/33 is replaced by coefficient 40/32 = 1.25 in relation (2).…”
Section: Stress Heat Flux Temperaturesupporting
confidence: 63%
“…The calculations have shown that this relation is not observed only in the area close to U 2 . The parabolic dependence up xx against velocity is identical to the proportional dependence of the transverse stress against the gas density in the shock wave described in [2,3], The results analogous to (2) were obtained also for the gas consisting of hard sphere molecules (k = oo) and in the case when k = 10. When k = oo the main difference is that coefficient 40/33 is replaced by coefficient 40/32 = 1.25 in relation (2).…”
Section: Stress Heat Flux Temperaturesupporting
confidence: 63%
“…We do not expect that this is a dense gas effect. Experimental [24][25][26] and numerical [27][28][29][30][31][32][33][34][35] data for dilute gases, from which the higher moments can be extracted, is available in the literature, but to the authors' knowledge, the effect has not been reported previously. The location where the higher out-of plane moments first deviate from zero does not depend on he order of the moment, i.e., the trend for the lower moments that the temperature (second moment) changes upstream of the flow velocity (first moment) and the density (zeroth moment) is not continued or it approaches a limit asymptotically.…”
Section: Discussionmentioning
confidence: 99%
“…Заметим, что эффект перехлёста продольной температуры является фундаментальным научным фактом. Данный эффект был обнаружен экспериментально [7] и получен строго теоретически на основе законов сохранения потоков массы и импульса в ударной волне [8]. Непосредственным следствием работы [8] является то, что любая новая теория, связанная с исследованием структуры фронта ударной волны, обязательно должна быть проверена на предмет совпадения с эталонной кривой для продольной температуры T x .…”
Section: относительная величина эффекта перехлёста эллипсоидальнойunclassified